A Clinician and Service User’s Perspective on Managing MS: Pleasure, Purpose, Practice - Hunter, Rachael (Frontiers in Psychology, 2020)
There is a growing body of evidence that points to an important role for modification of lifestyle factors and promotion of health-related quality of life in the secondary prevention of disease progression in multiple sclerosis (D’Hooghe, Nagels, Bissay., & De Keyser, 2010; Hadgkiss et al., 2014; Weiland et al., 2014). As a clinical psychologist diagnosed with multiple sclerosis in 2012 I have gained a unique insight into ways in which people living with MS and clinicians can usefully integrate evidence-based lifestyle modifications that enhance self-efficacy and self-management to improve wider psychological and physical health. The framework presented here enables clinicians to engage in salutogenic health promotion by placing value upon the importance of healthy, theoretically informed and evidence-based behaviour change. Furthermore, the framework provides a structure which can empower and provide guidance for people living with MS on what and how to implement and sustain behaviour change and emotional wellbeing in the face of this life-changing diagnosis.